Ecological Degradation, Disintegrating Psyches and Complicated Narratives: The Red and the White of Settler Colonies - Pal, Virender (International Journal of Psychosocial Rehabilitation, 2020)
In the recent times, many researches have pointed out that ecological degradation is playing havoc with the mental health of the human beings. Earlier this research was restricted to only scientific books, now the literary works around the world have started foregrounding the relationship between ecological degradation and the rising cases of insanity among the human beings. Native people around the world who were living their lives in the lap of nature were torn asunder from their homelands by the colonial forces. The mental problems are most prevalent among these communities. Now literature has started voicing concerns about ecological degradation and rising levels of pollution on the planet. Surprisingly the people who used to dismiss their way of life as barbaric are studying their techniques of preserving nature and maintaining balance between the human and the nonhuman elements of the ecosystem. Leslie Marmon Silko studies the relationship between ecological degradation and disintegration of human psyche in her famous novel Ceremony. The paper is a study of Leslie Marmon Silko’s novel Ceremony. Key words– ,